Online Marketing Communication Media Development of the Ban Wang Rang Yai Food Processing Community Enterprise to Add Value and Increase the Community Income at Makluea Kao Subdistrict, Sung Noen District, Nakhon Ratchasima Province - Khamcharoen, Pheerawish (Journal of Applied Informatics and Technology, 2024)
The objective of the research is 1) to study the product potential of the Ban Wang Rang Yai Food Processing Community Enterprise. 2) to create online media for the marketing communication of the Ban Wang Rang Yai Food Processing Community Enterprise at Makluea Kao Subdistrict, Sung Noen District, Nakhon Ratchasima Province. The research could add value and increase the community incomes. In addition, it was the research for development, which was conducted with the qualitative research methods. The tools were the interview form and the focus group. Then the content analysis was conducted. There were 15 key informants, included with the community development academicians in Sung Noen District, the marketing and marketing communication academicians and the members of the Ban Wang Rang Yai Food Processing Community Enterprise in Sung Noen District, Nakhon Ratchasima Province. The results revealed that 1) The Ban Wang Rang Yai food processing community enterprise had the potential in growing Hokkaido fresh milk corn. The group had the systems and processes for the production. The group also could build the careers and distribute the income within the community and the nearby communities and 2) the online marketing communication designed media ; the brands, the infographics, the online posters, the video clips, the product photos used for promoting on the page, the online brochure and LINE stickers, could extend the awareness of the identity and the brand. Moreover, the online media also could add the value to products and sustainably increase the community income.